2001
DOI: 10.1007/pl00007951
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-individual sources of variation in levels of urinary styrene metabolites

Abstract: Quantification of the intra- and inter-individual sources of variation provides useful information that can be used to design optimal sampling strategies, which would allow for the collection of sufficient data to estimate workers' exposures reliably when evaluating health risks associated with occupational contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Concentrations of urinary creatinine are frequently used to adjust the dilution of spot urine samples. We opted not to adjust for creatinine because, while correcting for dilution, it introduces inter-individual variation due to the fact that creatinine excretion rates are inXuenced by such factors as BMI, physical activity, diet and lean muscle mass (Symanski et al 2001;Viau et al 2004;Barr et al 2005). The levels of urinary 1-OHPG measured in the current study (range 0.04-3.27 ng/ml) were high compared to those we previously reported; mean levels in children (12-13 years) and their mothers (n = 300) ranged from 0.0158 § 0.0043 to 0.0645 § 0.0087 ng/ml among six diVerent regions in South Korea (Kang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of urinary creatinine are frequently used to adjust the dilution of spot urine samples. We opted not to adjust for creatinine because, while correcting for dilution, it introduces inter-individual variation due to the fact that creatinine excretion rates are inXuenced by such factors as BMI, physical activity, diet and lean muscle mass (Symanski et al 2001;Viau et al 2004;Barr et al 2005). The levels of urinary 1-OHPG measured in the current study (range 0.04-3.27 ng/ml) were high compared to those we previously reported; mean levels in children (12-13 years) and their mothers (n = 300) ranged from 0.0158 § 0.0043 to 0.0645 § 0.0087 ng/ml among six diVerent regions in South Korea (Kang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot of urine was collected at the end of shift concomitantly with other samplings and used for the determination of the styrene-specific urinary metabolites MA, PGA, 4-VPT, and regioisomeric PHEMAs. The methodologies have been described previously for MA and PGA (Symanski et al 2001), for 4-VPT (Manini et al 2002), and for the PHEMAs diastereomeric N-acetyl-S-(1-phenyl-2-hydroxyethyl)-cysteine (M1RR), (M1RS), and N-acetyl-S-(2-phenyl-2-hydroxyethyl)-cysteine (M2) (Ghittori et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Clayton et al (1999) evaluated correlations among pairs of longitudinal observations in the NHEXAS-Region 5 study and concluded that a single measurement provided a reasonable estimate of long-term exposure for some compounds (e.g., arsenic and lead in tap water) but not for others (e.g., VOCs in personal air). We followed the lead of others (Fleiss, 1986;Lemasters et al, 1996;Ryan et al, 2000;Symanski et al, 2001;Pang et al, 2002) in partitioning variance into between-and within-person components (Table 6) to evaluate the reliability of a single measurement with respect to a long-term average. The high intraclass correlation coefficient (r r ) of 0.76 for both lead in blood and chlorpyrifos in dust indicates that the observed variance was largely due to subject-specific differences and that measurements for a given individual were consistent over the study period of 1 year.…”
Section: Temporal Variability and Reliabilitymentioning
confidence: 99%